Consumers’ behavioral interests and sports services: Examining customer loyalty in Indonesian fitness centers - Muharram, Nur Ahmad; Pratama, Budiman Agung; Herpandika, Reo Prasetiyo; Weda; Kurniawan, Wing Prasetya; Puspodari; Maesaroh, Siti (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The development of the fitness industry in the world is increasing and has become an important issue in several countries, including Indonesia. Currently, the number of fitness participants in Indonesia has increased. An increase in fitness participants must be accompanied by an improvement in service quality, as poor service could risk a decrease in participants. The aim of this study was to examine the relationship between perceived quality, the perceived value of customers’ satisfaction, and future intentions in Kediri town. The sample consisted of 59 customers in 18 fitness industry centers. The data collection used a questionnaire technique, and the data analysis was based on the confirmatory factors and structural equation models. The research findings showed that the perceived satisfaction of clients greatly influences the value of loyalty and the location greatly influences the customers’ future intentions. Furthermore, there was a positive relationship between customer satisfaction and location factors with loyalty and future intentions. Perceived future loyalty and intentions influence customer satisfaction and the perceived importance of location in the fitness center. Consequently, perceived value positively affects both consumer loyalty and their future intentions.